Interaction of various types of rock and alkali-activated blast furnace slag - Mec, Pavel; Gembalová, Lucie (GeoScience Engineering, 2017)
Alkali-activated binders (AAB) are very intensively studied materials nowadays. Because of possible usage of secondary raw materials they can be environmentally efficient. Intensive research is focused especially on binder matrix, composition and its structure. For industrial usage it is necessary to work with some aggregate for preparation of mortars and concretes. Due to different structure of alkali-activated binders the interaction with aggregate will be different in compare to ordinary Portland cement binder. This paper deals with study of interaction of several types of rock used as aggregate and alkali-activated blast furnace slag. Research was focused especially on mechanical properties of prepared mortars.